2016
DOI: 10.4236/oje.2016.610057
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Woody Biomass, Carbon Stocks Potential in Selected Tropical Forest Patches of Tripura, Northeast India

Abstract: To estimate woody plant biomass stocks in different patches of forest ecosystems, total 20, 500 × 10 m (0.5 ha) sized line transects were laid in a protected area of Tripura, Northeast India. Overall, 9160 individuals were measured at ≥10 cm diameter at breast height (dbh) in 10 ha sampled area. Estimation of biomass suggested that highest coefficient for allometric relationships between density and biomass in 10 dbh classes was observed in bamboo brakes (R 2 = 0.90) than lowest for semi evergreen patch (R 2 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In addition to the carbon stocks, savannahs harbour a vast number of plant species and are important for global biodiversity (Abreu et al 2017). These plant species support ecosystem functions (Abreu et al 2017) and play a substantial role in the global carbon cycle (Majumdar et al 2016). However, tree cover in the savannahs is affected by deforestation and degradation, leading to climate change and biodiversity loss (Strassburg et al 2010, Thomas et al 2004, Talbot 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the carbon stocks, savannahs harbour a vast number of plant species and are important for global biodiversity (Abreu et al 2017). These plant species support ecosystem functions (Abreu et al 2017) and play a substantial role in the global carbon cycle (Majumdar et al 2016). However, tree cover in the savannahs is affected by deforestation and degradation, leading to climate change and biodiversity loss (Strassburg et al 2010, Thomas et al 2004, Talbot 2010.…”
Section: Introductionmentioning
confidence: 99%
“…As the culm density plays an important role in the level of aboveground biomass indicated by the correlation results, the increment in culm density especially in the older age class in the second year can be the determining factor for the amount of aboveground biomass. The present culm densities were higher than 7171culms/ha of Bambusa vulgaris from Ghana 20 (Table 5 ); from moso bamboo of China which reported a range of 3400–4220 culms/ha 21 ; from Majumdar et al 22 which reported 1088 culms/ha of Bambusa tulda from Tripura Northeast India; 1860 culms/ha of Bambusa tulda and 1364 culms/ha of Dendrocalamus strictus from Northern India 23 ; 7365 culms/ha of village bamboo grove from Assam Northeast India 19 and 2933 culms/ha of Bambusa vulgaris from Bangladesh 24 . However the present range was lower than Singnar et al 10 which reported a culm density of 39,075 culms/ha of Melocanna baccifera a monopodial bamboo from Assam.…”
Section: Discussionmentioning
confidence: 48%
“…A comparative study of aboveground biomass, C-storage and rate of C-sequestration is provided in Table 5 . The present rate of C-storage in aboveground biomass was higher than 20.92 Mg/ha of Bambusa tulda 22 ; 6.47 Mg/ha of Dendrocalamus strictus 23 and 13.96 Mg/ha of moso bamboo 26 . In some studies provided in Table 5 , the C-storage in aboveground biomass was not given.…”
Section: Discussionmentioning
confidence: 66%
“…Limited research carried out has used more than one or two indices for introduction and the analysis of patches [28]. However, in the present research, several metrics have been taken to quantify the spatial properties of the patches and its interpretation with the landscape ecology approach [29]. In fact, in this study the principles of the landscape ecology, a subset of ecology and geography; have been used to distribute and to disperse patches in different geographical directions, to change and to interpret in each direction.…”
Section: Discussionmentioning
confidence: 99%